2021
DOI: 10.51278/aj.v3i1.215
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Peran Guru dan Media Pembelajaran Terhadap Motivasi Berprestasi Siswa Jurusan Teknik Kendaraan Ringan SMK Negeri 4 Tana Toraja

Abstract: The article was to determine the effect of the role of teachers and learning media on the students’ achievement motivation of vehicle engineering department at State of Vocational High School (SMK N) 4 Tana Toraja. The researchers used quantitative methods. This type of research was correlational research. Because this study was to determine whether there is a relationship between the two variables. To find out the size or height of the relationship was expressed in the form of a correlation coefficient. Analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…In education units such as teacher performance schools become a very important support in the achievement of a school goal. [5] Since the passing of on Teachers and Lecturers in the World of Education Indonesia has undergone significant reforms. This law has the impact of expectations in improving the welfare and professionalism of teachers, because it mandates that education funds be allocated 20% of the State Budget.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In education units such as teacher performance schools become a very important support in the achievement of a school goal. [5] Since the passing of on Teachers and Lecturers in the World of Education Indonesia has undergone significant reforms. This law has the impact of expectations in improving the welfare and professionalism of teachers, because it mandates that education funds be allocated 20% of the State Budget.…”
Section: Introductionmentioning
confidence: 99%
“…According to [11] the foundation of teacher certification is: Legal, Psychological, Sociological, and Economic Foundation. The legal basis quoted in is, Law [10] (National Education System), [5] (Teachers and Lecturers), PP RI No. Based on this opinion, it can be concluded that teacher certification is a very important part of policy in improving the quality of teacher work to realize national education goals, for the sake of the future as an answer in the era of globalization as it is today, besides it is expected that certification can bring a big influence for teachers who have been certified coupled with increased welfare, so as to be the driver of teacher certification to improve its performance.…”
Section: Introductionmentioning
confidence: 99%